Formulasi Sediaan Tablet Effervescent dari Ekstrak Etanol Tanaman Bundung (Actionoscirpus grossus) sebagai Antioksidan - Noval Noval; Ilham Kuncahyo; Adam Ferdian Sigit Pratama; Syafira Nabillah; Roosma Hatmayana (Jurnal Surya Medika (JSM), 2021)
Bundung (Actinoscirpus grossus) is a plant that contains an antioxidant compound proven in previous studies, which has a moderate antioxidant or IC50 by 128 ppm. Antioxidant compounds can reduce the negative impact of oxidants, including metal binding enzymes and proteins. Antioxidant compounds act by donating one electron to the oxidant compound to inhibit oxidants activity. The purpose of this study was to formulate the Bundung plant extract into effervescent tablets, obtain effervescent samples that are physically stable, and can be used as antioxidants to inhibit free radicals in the body. The research method was experimental by using scoring parameters to determine the most optimal formulation. Physical evaluation includes organoleptic, weight uniformity, friability, hardness, and dissolving time. The results showed that the optimum formula was the formula I with a concentration of 68 mg of citric acid and sodium bicarbonate. Tablet effervescent is a brown color and characteristic odor of Bundung plant extract. Effervescent tablets have an weight uniformity (0.314 grams), friability (0.05%), hardness (7.75 ± 0.43 kg). Variations in citric acid and sodium bicarbonate concentration can affect uniformity, friability, hardness, and dissolving time. Room conditions cause this during the production process of effervescent tablets.